Społeczny ekshibicjonizm w Internecie jako nowe ryzykowne zachowanie polskiej młodzieży - Borzucka-Sitkiewicz , Katarzyna; Leksy , Karina (Studia Edukacyjne, 2020)
The technological progress and unlimited access to media create new possibilities of self-presentation in the public domain nowadays, especially for the young generation. The article presents a part of a broader research project which was aimed at defining the characteristics of behaviors shown in cyberspace by Polish students of upper-secondary schools and also at determining potential social and health consequences of such behaviors. The chosen fragment of the study mainly focuses on those actions that were considered as a sign of social exhibitionism on the Internet, such as uploading photos and videos, sharing private information about oneself and informing about current activity. The research was conducted in accordance with a quantity paradigm. It was of diagnostic and verification nature and a method of diagnostic survey with the use of questionnaires was applied.